Prosperity without growth economics for a finite planet - Jackson, Tim. (London Earthscan, 2011)
Is more economic growth the solution? Will it deliver prosperity and well-being for a global population projected to reach nine billion? In this explosive book, Tim Jackson - a top sustainability adviser to the UK government - makes a compelling case against continued economic growth in developed nations.
Includes index
Keywords: Sustainable development